Preservation of functionality, immunophenotype, and recovery of HIV RNA from PBMCs cryopreserved for more than 20 years - Dyer, Wayne B.; Suzuki, Kazuo; Levert, Angelique; Starr, Mitchell; Lloyd, Andrew R.; Zaunders, John J. (Frontiers in Immunology, 2024)
Background: Many research laboratories have long-term repositories of cryopreserved peripheral blood mononuclear cells (PBMC) which are costly to maintain but are of uncertain utility for immunological studies after decades in storage. This study investigated preservation of cell surface phenotypes and invitro functional capacity of PBMC from viraemic HIV+ patients and healthy seronegative control subjects, after more than twenty years cryopreservation.Methods: PBMC were assessed by 18-colour flow cytometry for major lymphocyte subsets within T, B, NK, and dendritic cells and monocytes. Markers of T cell differentiation and activation were compared with original immunophenotyping performed in 1995/6 on fresh blood at the time of collection.Functionality of PBMC was assessed by culture with influenza antigen or polyclonal T cell activation, to measure upregulation of activation-induced CD25 and CD134 (OX40) on CD4 T cells and cytokine production at day 2, and proliferative CD25+ CD4 blasts at day 7. RNA was extracted from cultures containing proliferating CD4+ blast cells and intracellular HIV RNA was measured using short amplicons for both the Double R and pol region pi code assays, while long 4Kbp amplicons were sequenced.Results: All major lymphocyte and T cell sub-populations were conserved after long-term cryostorage, except for decreased proportions of activated CD38+HLA-DR+ CD4 and CD8 T cells in PBMC from HIV+ patients. Otherwise, differences in T cell subpopulations between recent and long-term cryopreserved PBMC primarily reflected donor age-associated or HIV infection-associated effects on phenotypes. Proportions of naïve, memory and effector subsets of T cells from thawed PBMC correlated with results from the original flow cytometric analysis of respective fresh blood samples. Antigenspecific and polyclonal T cell responses were readily detected in cryopreserved PBMC from HIV+ patients and healthy control donors. Intracellular HIV RNA quantitation by pi code assay correlated with original plasma viral RNA load results. Full-length intracellular and supernatant-derived amplicons were generated from 5/12 donors, and sequences were ≥80% wild-type, consistent with replication competence.This unique study provides strong rationale and validity for using well-maintained biorepositories to support immunovirological research even decades after collection.